A case of angiographically verified non-occlusive mesentery ischemia induced by digitalis - Hasan KAYAHAN; Ömer TOPALAK; Yiğit GÖKTAY; Müjde SOYTÜRK; Murat MERAL; Karaca BAŞARAN; Özgür DAĞLAR (Turkish Journal of Gastroenterology, 2019)
-